Molecular mechanisms of novel selective glucocorticoid receptor agonist action in breast cancer cells - E. M. Zhidkova; V. P. Maksimova; D. D. Grigoreva; V. Z. Shirinian; M. G. Yakubovskaya; E. A. Lesovaya (Успехи молекулярной онкологии)
Introduction. Glucocorticoids (GC) are widely used in breast cancer (BC) therapy to reduce the side effects of cytostatic drugs and may exhibit antiproliferative effects on luminal BC cells. The biological action of GC is mediated by glucocorticoid receptor (GR) by two mechanisms: transrepression, which determines the therapeutic effect of GC, and transactivation (associated with the development of side effects, resistance to cytotoxic drugs, cancer progression and metastasis). Selective GR agonists (SEGRA) which may selective activate transrepression are a promising alternative to GC to use in combination cancer therapy. One of the most studied SEGRA is Compound A (CpdA). The instability of CpdA limits its use in clinical practice. So recently we performed synthesis and evaluation of biological activities of the CpdA analogue, CpdA-03.Aim. To compare the effects of SEGRA CpdA-03 and CpdA and dexamethasone on proliferative activity of breast cancer cells, as well as receptor nuclear translocation and activation of GR-dependent genes in breast cancer cells.Materials and methods. Luminal (MCF-7) and triple negative (MDA-MB-231) BC cell lines were used. The effect of CpdA-03 on proliferation was evaluated by direct counting of viable cells with trypan blue staining. The effect of the compound on cell distribution by cell cycle phases was assessed by flow cytofluorimetry with propidium iodide staining. Changes in the expression of GR-dependent genes after incubation with CpdA-03 were evaluated by quantitative polymerase chain reaction. Additionally, the ability of the new SEGRA to induce transactivation-associated translocation of the receptor to the nucleus was evaluated by Western blotting.Results. CpdA-03 was shown to suppress proliferation of luminal and triple negative BC cells. This compound causes changes in the expression of a number of GC-inducible genes, but does not stimulate GR phosphorylation and translocation to the nucleus in BC cells.Conclusion. The observed suppression of cell proliferation, as well as the ability of CpdA-03 to reduce gene expression of proteins regulating intercellular adhesion and cell migration, intracellular signaling, stress response, and transcription in BC cells makes it relevant for further development of the drug for use in the combination therapy of cancers including breast cancer.